On Models of Malaria with Natural Recovery - K, Adamu A.; M, Bulus S.; B, Williams; D, Yavalah (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study presents a mathematical model for malaria transmission dynamics, incorporating natural recovery and public awareness/sensitization within the human population. The model evaluates the impact of sensitization alongside conventional control strategies in mitigating malaria spread. Through qualitative analysis, the basic reproduction number was determined to be less than unity, suggesting the feasibility of disease control. Additionally, stability analysis confirmed that the disease-free equilibrium is locally and asymptotically stable. Our findings indicate that, with a combination of natural recovery, public sensitization, and conventional interventions, malaria can be successfully eradicated from the population.